State of charge estimation for rechargeable batteries - Chen, Can. (2013)
Rechargeable batteries will play a more and more important role in the future, as they are the essential in electronic vehicles (EVs)/hybrid electronic vehicles (HEVs) and as energy storage devices in distributed generation and portable equipment. Unfortunately, there are still many technological challenges to overcome for making full use of them. Consequently, this research is focused on an attractive one of the challenges as well as a very troublesome one, which is state of charge (SOC) estimation for rechargeable batteries.